THE EFFECT OF ENVIRONMENT PERFORMANCE, COMPANY IMAGE, AND MEDIA EXPOSURE TOWARDS CSR DISCLOSURE WITH COMPANY PROFILE AS MODERATING VARIABLE - Dara Sarra, Hustna; Alamsyah, Sustari (Dinasti Publisher, 2021)
It becomes highly necessary that every company has social responsibility to society and environment around in any forms of valuable contributions. However, it is believed that company itself will not expose widely regarding CSR activities provided or given for their own several logical reasons. The result of the research that has been conducted to 16 manufacturing companies shows that the environment performance, company image, and media exposure give positive and significant effects towards CSR Disclosure. On the other hand, this research shows that Company Profile variable is not suitable to take part as moderating variable. Through this essence, it is a must that every company should realize the importance of CSR Disclosure by means of delivering information in detail to stakeholders. Although the form of CSR is a kind of voluntary giving, still, the society and environment around have rights to obtain detail information regarding CSR activities which formed in CSR Disclosure.